Społeczne inicjatywy na rzecz organizacji opieki socjalnej nad ludźmi starymi w Królestwie Polskim na przełomie XIX i XX wieku. Zarys problematyki - Bołdyrew, Aneta (Biuletyn Historii Wychowania, 2019)
Lack of a universal pension system in the Kingdom of Poland in the late 19th and the early 20th centuries was one of the factors contributing to the difficult situation of the elderly from non-elite social strata, particularly in the face of insufficient support of the families. The homeless, who often also suffered from diseases, were crippled and begged, found themselves in a particularly difficult situation, men and women alike. Organising institutional social protection and medical care for this group required instant action. The priority was to establish homes for old people and various types of residential homes. This was primarily handled by charities for which medical care and welfare of the elderly were among the most important areas of activity. Old people’s homes were also established by religious communities and individualsas well as institutions operating on a self-help basis.